Calculați:
3√/11+(-2√11+9√/11)-10√11;
c (20√6+12√6)-(4√6-2√6);
b 2√2-(3√2-6√2 + √2)-√2
d (33√7-50√7)+(-3√7-5√7
( ex. 3).
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
Explicație pas cu pas:
a) 3√11+(-2√11+9√/11)-10√11 =
√11 (3-2 +9 -10 )=
√11 *0=
0
c) (20√6+12√6)-(4√6-2√6)=
20√6+12√6 -4√6+2√6=
√6 ( 20+12 -4+2) =
30√6
b) 2√2-(3√2-6√2 + √2)-√2=
2√2-3√2+6√2 - √2-√2 =
√2 ( 2-3+6-1-1 )=
3√2
d) (33√7-50√7)+(-3√7-5√7)=
33√7-50√7-3√7-5√7=
√7 ( 33-50-3-5 ) =
- 25√7
Alte întrebări interesante
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Fizică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă